1991
DOI: 10.1021/bi00106a006
|View full text |Cite
|
Sign up to set email alerts
|

Glucose analog inhibitors of glycogen phosphorylase: the design of potential drugs for diabetes

Abstract: The T-state crystal structure of the glucose-phosphorylase b complex has been used as a model for the design of glucose analogue inhibitors that may be effective in the regulation of blood glucose levels. Modeling studies indicated room for additional atoms attached at the C1-beta position of glucose and some scope for additional atoms at the C1-alpha position. Kinetic parameters were determined for alpha-D-glucose: Ki = 1.7 mM, Hill coefficient n = 1.5, and alpha (synergism with caffeine) = 0.2. For beta-D-gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
125
0
10

Year Published

1994
1994
2011
2011

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(142 citation statements)
references
References 75 publications
7
125
0
10
Order By: Relevance
“…The molecule makes a total of 12 hydrogen bonds and 63 van der Waals interactions, the most important of which are to side-chains of Leu 136, His 377, and Thr 378. In the a-D-glucose complex, there are, in total, 12 hydrogen bonds and 56 van der Waals contacts with a-D-glucose, but there is very little complementarity between the nonpolar groups of the sugar and nonpolar groups on the enzyme (Martin et al, 1991). The crystallographic analysis showed that the glucosyl moiety of I-GlcNAc made one less hydrogen bond to the protein than in the a-D-glucose complex.…”
Section: Refined Structurementioning
confidence: 98%
See 3 more Smart Citations
“…The molecule makes a total of 12 hydrogen bonds and 63 van der Waals interactions, the most important of which are to side-chains of Leu 136, His 377, and Thr 378. In the a-D-glucose complex, there are, in total, 12 hydrogen bonds and 56 van der Waals contacts with a-D-glucose, but there is very little complementarity between the nonpolar groups of the sugar and nonpolar groups on the enzyme (Martin et al, 1991). The crystallographic analysis showed that the glucosyl moiety of I-GlcNAc made one less hydrogen bond to the protein than in the a-D-glucose complex.…”
Section: Refined Structurementioning
confidence: 98%
“…At the allosteric site, apparent features of the difference map indicated ( I ) a shift of the side chain of Arg 309 in order to optimize contacts with the nucleotide phosphate group, (2) a small change in the position of Tyr 75, and (3) displacement of a few water molecules near the nucleotide base. At the catalytic site, the main features of the difference map included: ( I ) the presence of negative den- 14 86 17 83 16 84 18 82 14 86 sity over His 377, and associated positive density nearby, indicating a shift of the side-chain of histidine away from the I-GlcNAc molecule to optimize contact with the glucosyl0-6 hydroxyl; this movement is seen for all complexes with glucose-like compounds (Barford et al, 1988;Oikonomakos et al, 1988;Martin et al, 1990Martin et al, , 1991Papageorgiou et al, 1991), and (2) the presence of negative density near the 0 -2 hydroxyl indicating displacement of a water molecule (Wat 9.904).…”
Section: X-ray Crystallography Difference Fouriermentioning
confidence: 99%
See 2 more Smart Citations
“…The difference electron density maps for PL-GPb-phosphate-Glc-IMP and PL-GPb-fluorophosphateGlc-IMP complexes against PL-GPb-phosphite-Glc-IMP complex, in the vicinity of the catalytic site, are shown in Figure 3. In the X-PLOR refined structures of the three complexes, the conformational changes in the enzyme are small and similar to those observed when Glc (Martin et ai., 1990) or a Glc-like inhibitor (Martin et al, 1991;Oikonomakos et al, 1995) binds. We describe in some detail mainly the PL-GPb-phosphate-b-GIc-IMP complex.…”
Section: X-ray Crystallographymentioning
confidence: 99%